IMPLEMENTASI E-MODUL HIDROLISIS GARAM BERBASIS PROBLEM BASED LEARNING DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP HASIL BELAJAR KOGNITIF MURID SMAN 4 PADANG - Aprina Martin, Laras; Iryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Salt hydrolysis is one of the chemistry topics in Grade XI Phase F that is considered difficult because it requires mastery of prerequisite concepts. Based on observations conducted at SMAN 4 Padang, approximately 50% of students had not achieved the Learning Objective Achievement Criteria (KKTP). Learning was still dominated by the use of textbooks, PowerPoint presentations, and student worksheets (LKPD), while the use of e-modules as digital teaching materials remained limited. One effort to address this problem is the implementation of a salt hydrolysis e-module based on Problem-Based Learning (PBL) with the Teaching at the Right Level (TaRL) approach. This study aimed to determine the effect of implementing the Problem-Based Learning (PBL)-based salt hydrolysis e-module with the Teaching at the Right Level (TaRL) approach on the cognitive learning outcomes of students at SMAN 4 Padang. The study employed a quasi-experimental method using a nonequivalent control group design. The sample consisted of 31 students in the experimental class and 31 students in the control class selected through purposive sampling. Data were collected using a 15-item multiple-choice objective test and analyzed using the Independent Samples t-test and the N-gain test. The results showed that the mean posttest score of the experimental class (86.97) was higher than that of the control class (80.39). The experimental class achieved an N-gain score of 0.8334, which was higher than the control class (0.7476). The hypothesis test showed that the calculated t value (2.811) was greater than the t-table value (2.000), with a Sig. (2-tailed) value of 0.007 < 0.05, indicating a significant difference in learning outcomes between the two classes. Therefore, the implementation of the Problem-Based Learning (PBL)-based salt hydrolysis e-module with the Teaching at the Right Level (TaRL) approach had a positive effect on the cognitive learning outcomes of students at SMAN 4 Padang.